Comparing exercise interventions to increase persistence with physical exercise and sporting activity among people with hypertension or high normal blood pressure: study protocol for a randomised controlled trial - Fife-Schaw, C; de Lusignan, S; Wainwright, J; Sprake, H; Laver, S; Heald, V; Orton, J; Prescott, M; Carr, H; O'Neill, M (BioMed Central, 2014)
Background: Increasing physical activity is known to have health benefits for people with hypertension and related conditions. Current general practitioner referrals for gym-based exercise increase physical activity but meta-analyses show that while these are effective the absolute health risk reduction is small due to patients failing to maintain activity levels over time. This study assesses the effectiveness of two sports-oriented interventions that are intended to bridge the intention-behaviour gap and thus increase the likelihood of sustained increases in physical activity. Methods/design: Four-arm randomised controlled trial. The study tests two types of intervention that are intended to increase physical activity among currently inactive 18- to 74-year-old people with hypertension or high-normal blood pressure. This study will assess the effectiveness of a 12-week sports-oriented exercise programme, the efficacy of a web-delivered self-help tool to promote and support sports participation and healthy behaviour change and the effect of these interventions in combination. The control arm will be a standard care general practitioner referral for gym-based exercise. Participants will be allocated using block randomisation. The first author and primary analyst is blinded to participant allocation. The primary outcome measures will be time spent in physical activity assessed in metabolic equivalent minutes per week using the International Physical Activity Questionnaire 1 year after commencement of the intervention. Secondary outcomes include increased involvement in sporting activity and biomedical health outcomes including change in body mass index, and waist and hip measurement and reductions in blood pressure. Discussion: If proven to be superior to general practitioner referrals for gym-based exercise, these sports-oriented interventions would constitute low-cost alternatives. The next stage would be a full economic evaluation of the interventions. Trial Registration: Current Controlled Trials ISRCTN71952900 (7 June 2013).